Phosphorylation status of CPK28 affects its ubiquitination and protein stability. Issue 4 (2nd December 2022) - Liu, Xiaotong; Zhou, Yuanyuan; Chen, Kexin; Xiao, Zejun; Liang, Xuelian; Lu, Dongping
Summary: Plant innate immunity is tightly regulated. The Arabidopsis thaliana CALCIUM‐DEPENDENT PROTEIN KINASE28 (CPK28) functions as a negative immune regulator. We recently demonstrate that CPK28 undergoes ubiquitination that is mediated by two ubiquitin ligases, ARABIDOPSIS TÓXICOS EN LEVADURA31 (ATL31) and ATL6, which results in its proteasomal degradation. CPK28 undergoes both intermolecular autophosphorylation and BIK1‐mediated phosphorylation. However, whether the phosphorylation status of CPK28 dictates its ubiquitination and degradation is unknown yet. We used immune response analysis, transient degradation system, ubiquitination assays, co‐immunoprecipitation, and other biochemical and genetic approaches to investigate the effect of the phosphorylation status of CPK28 on its degradation mediated by ATL31/6. We found the mutation of Ser318 (a site of both intermolecular autophosphorylation and BIK1‐mediated phosphorylation) or a BIK1 phosphorylation site on CPK28 leads to its compromised association with ATL31 and reduced ubiquitination by ATL31. Moreover, we confirm the previous findings that two CPK28s can interact with each other, which likely promotes the intermolecular autophosphorylation. We also show that the phosphorylation status of CPK28 in turn affects its intermolecular association. We demonstrate that the phosphorylation status of CPK28 affects its degradation mediated by ATL31. Our findings reveal a link between phosphorylation of CPK28 and its ubiquitination and degradation.